2022
DOI: 10.1136/jnnp-2022-328797
|View full text |Cite
|
Sign up to set email alerts
|

Impact of previous disease-modifying treatment on safety and efficacy in patients with MS treated with AHSCT

Abstract: BackgroundAutologous haematopoietic stem cell transplantation (AHSCT) is a highly effective treatment for multiple sclerosis (MS). The impact of previous long-lasting disease-modifying treatments (DMT) for safety and efficacy of AHSCT is unknown.ObjectiveTo explore whether previous DMTs with long-lasting effects on the immune system (anti-CD20 therapy, alemtuzumab and cladribine) affect treatment-related complications, long-term outcome and risk of new MS disease activity in patients treated with AHSCT.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Since newborn screening for GLD is not widely available ( Wasserstein et al, 2021 ; Schrier Vergano et al, 2022 ), new therapeutic approaches such as immunotherapies may be warranted. Applying immunotherapies could extend the therapeutic window for hematopoietic stem cell transplantation ( Kvistad et al, 2022 ) or enhance long-term outcomes from interventions such as gene therapy ( Heller et al, 2021 ; Hordeaux et al, 2022 ), and therein provide greater benefit to more patients. Future studies to address these issues should examine whether existing FDA-approved immunomodulatory therapeutics can modify GLD disease, both as a monotherapy and as a means to mitigate the early stages of disease and potentially expand eligibility among patients to qualify for other therapies.…”
Section: Resultsmentioning
confidence: 99%
“…Since newborn screening for GLD is not widely available ( Wasserstein et al, 2021 ; Schrier Vergano et al, 2022 ), new therapeutic approaches such as immunotherapies may be warranted. Applying immunotherapies could extend the therapeutic window for hematopoietic stem cell transplantation ( Kvistad et al, 2022 ) or enhance long-term outcomes from interventions such as gene therapy ( Heller et al, 2021 ; Hordeaux et al, 2022 ), and therein provide greater benefit to more patients. Future studies to address these issues should examine whether existing FDA-approved immunomodulatory therapeutics can modify GLD disease, both as a monotherapy and as a means to mitigate the early stages of disease and potentially expand eligibility among patients to qualify for other therapies.…”
Section: Resultsmentioning
confidence: 99%
“…For patients with malignant hematological diseases, such as MM, NHL, and HL, AHSCT can potentially prolong survival [ 42–44 ]. Whether sufficient HSCs can be mobilized is the key to the success of transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis (2022) showed that, compared with before treatment, aHSCT reduced the frequency of MS relapses, and MRI activity decreased disability (EDSS score), and promoted NEDA (68% of patients) [ 88 ]. Retrospective observational data suggest that aHSCT is effective in patients with insufficient response to previous IRT [ 89 ]. Further observational data suggested that aHSCT was more effective in preventing relapses than fingolimod (hazard ratio [HR] 0.55 [95% CI 0.37–0.91]), with a greater likelihood of improvement in EDSS score (HR 2.62 [95% CI 1.46–4.72]); the efficacy of aHSCT and natalizumab was broadly similar [ 90 ].…”
Section: A Note On Autologous Haematopoietic Stem Cell Transplantatio...mentioning
confidence: 99%